Methods for Improving lighting Inside Educational Buildings and Their Role in Improving Visual Performance Case study: A Classroom in the City of Tama, Sohag Governorate سبل الارتقاء بالإضاءة داخل المباني التعليمية ودورها في تحسين الاداء البصرى بها (دراسة حاله: أحد الفصول الدراسية بالمدارس بمدينة طما محافظه سوهاج) - Mai Hamdy Abd ElLatif Abd ElLatif; Ahmed Abd ElRahim Farghaly Farghaly; Mohamed Helmy Al-Morsy Al-Hafnawy (JES: Journal of Engineering Sciences)
Natural light and artificial light are two essential factors in classrooms. Natural lighting contributes to increasing the intellectual and physical performance of both students and teachers, thus enhancing the learning process within the classroom. There is no doubt that the classroom cannot be lit by natural lighting only throughout the whole day, so artificial lighting is necessary. The research problem appears in the presence of glare due to natural lighting, also an increase or decrease in its percentage beyond the permissible limit, which causes the lack of visual comfort within the classroom. Therefore, The research paper aims to study the determinants and factors that affect lighting inside the classroom, and then determine the appropriate processors and choose the best ones to improve visual performance and achieve visual comfort within it. This was applied to a school in the city of Tema, Sohag Governorate, as a model for schools in desert environments with high solar radiation, using the (Design Builder program) as a simulation program. The study found that the determinants that affect lighting condition in existing buildings are sun breakers, type of glass, colour of walls and ceilings, and artificial lighting. It was found that a compound of breakers with a protrusions of (0.75 meters) for the western facade classrooms achieves the highest percentage in reducing the percentage of natural lighting and reaching the permissible limit in lighting, which is (300: 2000 lux), with regard to studying at open and closed windows, and during winter and summer time at all times of the day. الملخص يعدالضوء الطبيعي والصناعي عنصران أساسيان داخل الفصول الدراسية، حيث تسهم الإضاءة الطبيعية في دعم الأداء الفكري والبدني لكل من الطلاب والمعلمين ومن ثم تعزيز العملية التعليمية، ومما لا شك فيه أن الأنشطة التي تدور بالفصل الدراسي يصعب دعمها من خلال الإضاءة الطبيعية فقط على مدار اليوم، ولذلك فأن الإضاءة الصناعية تصبح ضرورية. وتظهر الإشكالية البحثية في وجود إبهار بسبب الإضاءة الطبيعية وكذلكزيادة أو نقصان نسبتها عن الحد المسموح به، مما يسبب عدم الراحة البصرية داخل الفصل الدراسي. لذا يهدف البحث إلي دراسة المحددات والعوامل التي تؤثر علي الإضاءة داخل الفصل الدراسي ومن ثم تحديد المعالجات المناسبة واختيار الأفضل لتحسين الأداء البصري وتحقيق الراحة البصرية داخله. وقد تم تطبيق ذلك على مدرسة في مدينة طما بمحافظة سوهاج, كنموذج لمدارس البيئات الصحراوية ذات الإشعاع الشمسي العالي, وذلك باستخدام برنامج design builder كأحد برامج المحاكاة.  وتوصلت الدراسة إلي أن المحددات التي تؤثر علي الإضاءة في المباني القائمة وتحتاج الي التعديل هي الكاسرات الشمسية ونوع الزجاج وأن المحددات المتحققة والتي لا تحتاج الي تدخل هي لون الحوائط والأسقف والإضاءة الصناعية، وتبين أن الكاسرة المركبة ببروز 0.75 متر لفصول الواجهة الغربية تحقق النسبة الأعلى في تقليل نسبة الإضاءة الطبيعية والوصول إلي الحد المسموح به في الإضاءة هو من (300: 2000 لوكس) وذلك بالنسبة للدراسة علي النوافذ المفتوحة والمغلقة، وفي فصل الشتاء والصيف لجميع الاوقات باليوم.